Iterative Assembly of Chiral Alcohols Utilizing CMMP-Mediated Mitsunobu Reactions - Kitamura, Kei; Ise, Saki; Tsunoda, Tetsuto; Kaku, Hiroto (Synthesis, 2023)
An iterative assembly of chiral alcohol building blocks is reported utilizing cyanomethylene trimethylphosphorane (CMMP)-mediated Mitsunobu reactions. 1,3-Benzodithiole tetraoxide (BDT) was used as the platform to prepare long-chain saturated compounds with multiple stereocenters en route to polyisoprenoid natural products. Selectively protected chiral 1,3-butanediols played a key role in iterative chain elongation for the construction of 1,5-dimethyl branched arrays with high stereocontrol.
Keywords: Mitsunobu reaction; BDT; chiral alcohols; stereochemistry; polyisoprenoids; CMMP; desulfonylation